2004
DOI: 10.1111/j.1460-9568.2004.03721.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and spontaneous neurogenesis in the postnatal slice culture of rat hippocampus

Abstract: Organotypic slice culture preserves the morphological and physiological features of the hippocampus of live animals for a certain time. The hippocampus is one of exceptional regions where neurons are generated intrinsically and spontaneously throughout postnatal life. We investigated the possibility that neurons are generated continuously at the dentate granule cell layer (GCL) in slice culture of the rat hippocampus. Using 5-bromodeoxyuridine (BrdU) labelling and retrovirus vector transduction methods, the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…Not only the extracellular architect but also the synaptodendritic interactions are reconstituted in slice cul- tures (18). In addition, the presence of neurogenesis has been reported to happen in hippocampal slice cultures (28,45). For these reasons, slice cultures have been used widely to study the morphology and plasticity of the hippocampus.…”
Section: Inhibitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Not only the extracellular architect but also the synaptodendritic interactions are reconstituted in slice cul- tures (18). In addition, the presence of neurogenesis has been reported to happen in hippocampal slice cultures (28,45). For these reasons, slice cultures have been used widely to study the morphology and plasticity of the hippocampus.…”
Section: Inhibitionmentioning
confidence: 99%
“…Intrinsic and spontaneous neurogenesis are reported to take place at the DG in organotypic hippocampal slice cultures (28,45). To investigate the dysfunction of neuronal cell development in hippocampal slice cultures exposed to HIV-MDM or rVpr, we labeled endogenous precursor cells in the slices using an EGFP-expressing MLV vector (SR␣-EGFP).…”
Section: Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have confirmed that neurogenesis continues in discrete regions of the adult brain, especially in the subgranular zone (SGZ) of the dentate gyrus (DG) and the subventricular zone (SVZ) of the lateral ventricles [1,2]. During adult hippocampal neurogenesis, newly generated cells can proliferate, differentiate, mature, and integrate into functional neural networks [3].…”
Section: Introductionmentioning
confidence: 99%